2020
DOI: 10.1093/ageing/afaa231
|View full text |Cite
|
Sign up to set email alerts
|

The association of weight change and all-cause mortality in older adults: a systematic review and meta-analysis

Abstract: Objective there may be age-related differences in the impact of weight change on health. This study systematically reviewed the evidence on the relationship between weight change and all-cause mortality in adults aged 65 years and older. Methods MEDLINE, EMBASE and CINAHL were searched from inception to 11 June 2020, PROSPERO CRD 42019142268. We included observational studies reporting on the association between weight change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 28 publications
4
46
2
Order By: Relevance
“…In the present study, weight gain was not significantly associated with all-cause mortality risk nor CVD or cancer-specific mortality. This contrasts the findings of meta-analyses, which have reported a modest but significant associations between weight gain and all-cause mortality [ 21 , 28 , 32 ]. This could possibly be impacted by the obesity paradox, supported by epidemiological studies in older adults that overweight and obesity may not affect all-cause or specific cause of mortality [ 33 ].…”
Section: Discussioncontrasting
confidence: 98%
See 3 more Smart Citations
“…In the present study, weight gain was not significantly associated with all-cause mortality risk nor CVD or cancer-specific mortality. This contrasts the findings of meta-analyses, which have reported a modest but significant associations between weight gain and all-cause mortality [ 21 , 28 , 32 ]. This could possibly be impacted by the obesity paradox, supported by epidemiological studies in older adults that overweight and obesity may not affect all-cause or specific cause of mortality [ 33 ].…”
Section: Discussioncontrasting
confidence: 98%
“…The present findings are consistent with the results of previous meta-analyses on the association between weight loss and mortality risk [ 21 , 28 , 32 ]. For example, a recent systematic review and meta-analysis reported that weight loss was associated with a 59% increased mortality risk in adults aged 65 years or over [ 21 ]. Results of another meta-analysis indicated a 67% increase in all-cause mortality risk associated with weight loss among adults aged 60 years or over [ 28 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…For example, a meta-analysis of thirty studies showed that older adults who had a non-stable weight trajectory (either weight gain, weight loss, or weight cycle) had a higher mortality rate compared to those with stable weight. 1 Phenome-wide association studies (PheWAS), which have the capacity to examine associations of an exposure of interest across the full disease phenome, allow us to test associations between weight trajectory and health status in large-scale electronic health records (EHR), which contain longitudinal data for a large patient population, including frequent objective weight measures, taken as part of typical clinic visits. To date, weight-related PheWAS have used body mass index (BMI)-related genetic scores [2][3][4] /variants 5 or average BMI values 6 as the exposure of interest, but have not yet explored the phenome-wide consequences of longitudinal weight trajectories.…”
Section: Introductionmentioning
confidence: 99%